Evaluasi Kebijakan Pelayanan Administrasi Terpadu Kecamatan (Paten) Di Kecamatan Ciledug Kota Tangerang - Shefika Candra Kirana (Jurnal Riset Sosial Humaniora dan Pendidikan, 2023)
Problems in public services are often encountered in their implementation even though standards and laws have been established. In the evaluation of the PATEN policy in Ciledug District, Tangerang City, there are problems including the timeliness of service, service costs, and supporting resources for service implementation. The government has attempted to bring about an innovation in the field of public services through the District Integrated Administrative Services (PATEN) policy regulated in Permendagri Number 4 of 2010, which contains the delegation of authority from regents to sub-district heads. Following up on the Permendagri, the government of Tangerang City has implemented integrated sub-district administration services, especially in Ciledug District. This type of research is a qualitative research with a descriptive research type. The writing method used is the literature study research method, a series of activities related to the method of collecting library data, reading and taking notes, and processing research materials. The results showed that the implementation seen from the aspect of service costs was sufficient and according to fairness standards and from the aspect of service time and supporting resources for the implementation of services was inadequate. The purpose of the District Integrated Administrative Services has not been optimally achieved because the type of delegation of authority given is considered not to be effective and efficient in creating quality services and getting closer to the community. The advice given is to add service support facilities and improve service methods so that service times are better, as well as to review the types of delegation of authority given to sub-district heads so that the policy objectives are achieved more optimally.